Non-antimicrobial airway management of non-cystic fibrosis bronchiectasis - Ashley M. Egan; Jeremy M. Clain; Patricio Escalante (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases, 2018)
Bronchiectasis are often encountered in clinical practice, and are characterized by abnormal airway dilatation and distortion associated with impaired mucociliary clearance and mucous plugging, which are frequently associated with recurrent infections. Numerous etiologies can underlie the development of bronchiectasis, but the most important distinction in research and clinical practice is between bronchiectasis due to cystic fibrosis (CF) and bronchiectasis due to all other reasons (non-CF bronchiectasis). The causes of non-CF bronchiectasis are varied and often unclear. Patients disease severity and phenotypes of non-CF bronchiectasis also varied, which can influence disease trajectory, frequency of exacerbations and mortality. This article reviews the published evidence and suggests interventions to enhance airways clearance in patients with non-CF bronchiectasis, which are key components of an individualized therapeutic program in order to achieve symptomatic relief and prevention of exacerbations and functional decline.